Molecular taxonomy of some sponges (Demospongiae) using ribosomal (18s rrna) and partial mitochondrial (coi) genes - Dat, Ton That Huu; Cuc, Nguyen Thi Kim; Cuong, Pham Viet (Academia Journal of Biology, 2018)
Sponges, the most ancient multicellular metazoan, were widely distributed across habitats. Vietnam is known to possess a high biodiversity of sponges, however, they are mostly identified based on morphological characteristics and lack the molecular data. In the current study, the phylogenetic relationship of some sponges (Demospongiae) in Vietnam was constructed using two independent markers (COI and 18S rRNA). In this paper the individual markers (COI and 18S rRNA) were successfully used to identify some sponge taxa at the species level. The obtained results showed the congruence of molecular taxonomy using two independent markers. However, our study showed that a combination of the two markers provided more information and supported better for sponge identification. At order level, the COI tree and 18S rRNA tree also recovered the same clades, indicating the congruence of COI and 18S rRNA genes in sponge classification. However, branching order of the clades in COI tree was weakly supported and slightly different from those in 18S rRNA tree.